Complexity and Project Management: A General Overview - José R. San Cristóbal; Luis Carral; Emma Diaz; José A. Fraguela; Gregorio Iglesias (Complexity)
As projects have become more and more complex, there has been an increasing concern about the concept of project complexity. An understanding of project complexity and how it might be managed is of significant importance for project managers because of the differences associated with decision-making and goal attainment that are related to complexity. Complexity influences project planning and control; it can hinder the clear identification of goals and objectives, it can affect the selection of an appropriate project organization form, or it can even affect project outcomes. Identifying the different concepts associated to project complexity, its main factors and characteristics, the different types of project complexity, and the main project complexity models, can be of great support in assisting the global project management community. In this paper, we give a general overview of how complexity has been investigated by the project management community and propose several ideas to address this topic in the future.